Antibacterial efficacy of novel bismuth-silver nanoparticles synthesis on Staphylococcus aureus and Escherichia coli infection models - Castro-Valenzuela, Beatriz Elena; Franco-Molina, Moisés Armides; Zárate-Triviño, Diana Ginette; Villarreal-Treviño, Licet; Kawas, Jorge R.; García-Coronado, Paola Leonor; Sobrevilla-Hernández, Gustavo; Rodríguez-Padilla, Cristina (Frontiers in Microbiology, 2024)
The emergence of multi-drug resistant bacteria is one of the main concerns in the health sector worldwide. The conventional strategies for treatment and prophylaxis against microbial infections include the use of antibiotics. However, these drugs are failing due to the increasing antimicrobial resistance. The unavailability of effective antibiotics highlights the need to discover effective alternatives to combat bacterial infections. One option is the use of metallic nanoparticles, toxic to some microorganisms due to their nanometric size. Therefore, the objectives of this study were 1) to synthesize and characterize bismuth and silver nanoparticles, 2) to evaluate the antibacterial activity of NPs against Staphylococcus aureus and Escherichia coli in several infection models (in vivo models: infected wound and sepsis, and in vitro model: mastitis) and 3) determine the cytotoxic effect on several cell lines representative of the skin tissue. We obtained bimetallic nanoparticles of bismuth and silver in stable aqueous solution from a single reaction by chemical synthesis. These nanoparticles show antibacterial activity on S. aureus and E. coli in vitro without cytotoxic effect on fibroblast, endothelial vascular and mammary epithelium cell lines. In an infected-wound mice model antibacterial effect was observed, nonetheless without effect on an in vitro mastitis and sepsis model.